MSME Financial Transformation: The Vital Role of Banking in Innovation and Service Provision - Utama, Ahmad Nur Budi; Suryani, Ade Irma; Hamdiah, Hamdiah; Dhonal, Rama (Journal of Social Science and Business Studies, 2024)
The purpose of this research is to analyze the vital role of banking in supporting the financial transformation of MSMEs through financial service innovation in Jambi City and to identify and evaluate the impact of innovative financial services provided by banks on the growth and development of MSMEs in the process of financial transformation in Jambi City. This study employs qualitative research methods and utilizes data collection techniques such as in-depth interviews, participatory observations, and content analysis to obtain a comprehensive understanding of the research topic. The findings indicate that banking plays a crucial role in facilitating MSMEs' access to financial services essential for business growth. Banking support, particularly through financial service innovation, is the key to MSME transformation. By adopting new technologies and financial solutions, MSMEs can manage their finances more efficiently and optimize business growth. The study also highlights the importance of financial education for MSMEs. Banks can act as knowledge providers, offering insights into effective financial management, enabling MSMEs to become more competitive in the market. The financial transformation of MSMEs requires strong collaboration between banks, MSMEs, and the government to create an inclusive and sustainable financial ecosystem.